Influence of Palm Sugar Water in the Native Chicken Performance - Fera Aryanti; Muhammad Bayu Aji; Nugroho Budiono (Jurnal Sain Veteriner, 2013)
Abstract Palm sugar containing 66,18% sukrose is an additional source of energi quickly available to the chicken. A study to examine the effect of palm sugar in the native chicken performance was held in animal health training center, Cinagara-Bogor lasted from August until November 2012. This present experiment using 1274 native chicken that were kept starting DOC. Palm sugar concentrations given in the drinking water as much as one percent started to be given to the chcken when they were still DOC. After that, the palm sugar water was given continously intermittent interval by administering multivitamin. The control group was not given the palm sugar. Chicken aged 0 to 6 weeks were given palm sugar twice a day. After reaching over 6 weeks old, palm sugar water was only given onece a day. Result obtained showed that the administration of palm sugar water affected the increase in body weight gain, feed consumption and lower mortality as well. The result also showed that the FCR is lower than that of the control group until 6 weeks old.